2013
DOI: 10.3758/s13415-013-0149-7
|View full text |Cite
|
Sign up to set email alerts
|

An ERP investigation of visual word recognition in syllabary scripts

Abstract: The bi-modal interactive-activation model has been successfully applied to understanding the neuro-cognitive processes involved in reading words in alphabetic scripts, as reflected in the modulation of ERP components in masked repetition priming. In order to test the generalizability of this approach, the current study examined word recognition in a different writing system, the Japanese syllabary scripts Hiragana and Katakana. Native Japanese participants were presented with repeated or unrelated pairs of Jap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 30 publications
5
27
1
Order By: Relevance
“…This, in addition to the clearly distinct spatial distribution of the effect, points to different underlying neural generators compared with the lexically driven N400 effects. Furthermore, the different pattern of early priming effects seen for Katakana and Hiragana in the present study contrasts with the absence of any differential priming for the two scripts reported in our prior work with visual primes and targets (Okano et al, 2013). Most important is that cross-script repetition priming effects (i.e., the same spoken word written in one script for the prime and the other script for the target) were found not to interact with script, and emerged later (in the N250 time window) than the early priming effect of the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This, in addition to the clearly distinct spatial distribution of the effect, points to different underlying neural generators compared with the lexically driven N400 effects. Furthermore, the different pattern of early priming effects seen for Katakana and Hiragana in the present study contrasts with the absence of any differential priming for the two scripts reported in our prior work with visual primes and targets (Okano et al, 2013). Most important is that cross-script repetition priming effects (i.e., the same spoken word written in one script for the prime and the other script for the target) were found not to interact with script, and emerged later (in the N250 time window) than the early priming effect of the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Most important is that cross-script repetition priming effects (i.e., the same spoken word written in one script for the prime and the other script for the target) were found not to interact with script, and emerged later (in the N250 time window) than the early priming effect of the present study. Okano et al (2013) argued that the cross-script N250 priming effects they observed were likely driven by the phonology shared by primes and targets in different scripts. This therefore suggests that the early priming effect found in the present study is likely subtended by a different mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, the data from adults and developing children suggest that any potential differences between masked priming effects in Semitic and Indo-European words are not qualitative. Indeed, there is evidence suggesting that the mechanisms underlying visual word recognition are also similar in other writing systems (e.g., the hiragana and katakana scripts of Japanese; see Okano, Grainger, & Holcomb, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the literature review, it goes on to construct the theoretical framework for the present study, which includes: LCCM Theory (the Theory of Lexical Concepts and Cognitive Models) (Evans, 2006(Evans, , 2009 [1], the Usage-Based Theory of Language Acquisition (Langacker, 1987(Langacker, , 1991Tomasello, 2003) and the Theory of Personal Experience (Dai, 2007). [2]With the theoretical framework serving as the guideline, the word test and the questionnaire are designed to examine the formation and development of Chinese EFL learners' English mental lexicon at three different developmental stages.…”
Section: Introductionmentioning
confidence: 99%